The New Trend for A Sustainable Regeneration of Built Environment: Green Solutions and Digital Twin for Human Centres Design and Well-Being (International Journal of Architecture and Urbanism, 2025)
During the period when we were confined to our homes, engaging with family members around the clock and interacting with the world digitally while conducting remote work, numerous shortcomings in the architectural design of our buildings and indoor comfort levels became apparent. A significant issue highlighted by this experience was the lack of natural elements in living spaces, particularly the absence of green areas and vegetation, which are often considered exclusive features of luxury homes, offices, or villas. This paper explores how we focused on improving the ecological quality of building environments through a retrofitting project of existing office buildings in the historic city of Lucca, Tuscany. The eco-systemic design approach, pioneered by the Bexlab team at the University of Florence, not only supported and compared various retrofitting scenarios through digital twin simulations, but also emphasized the importance of integrating natural living spaces. This initiative aimed to foster a new connection between inhabitants, architecture, technology, and nature.